Non-Cooperative Target Ranging Based on High-Orbit Single-Star Temporal–Spatial Characteristics - Derui Zhang; Hao Wang; Qing Zhao (Applied Sciences)
A visible light camera payload with star-sensitive functionality was installed to measure the distance between a non-cooperative target satellite and a high-orbit satellite. The rotation matrix was used to calculate the pointing vector from the center of the satellite’s star-sensitive camera axis to the target satellite. Multiple position imaging was achieved, and the moving window approach was used to establish two sets of equations relating the pointing vectors to the positions of binary satellites. To simplify the calculations, the target satellite’s eccentricity was assumed to be small (0 to 0.001), allowing elliptical orbits to be approximated as circular. Additionally, short-interval (1-min) imaging measurements were taken, assuming a small inclination of the target satellite (0.0° to 0.4°). This resulted in the construction of a ranging model with high accuracy, producing a ranging error of less than 5% of the actual distance.